Effect of Processing on Flavour Precursors, Pyrazines and Flavour Quality of Malaysian Cocoa Beans - Hashim, Puziah (1997)
Studies were conducted to determine the effect of processing (fermentation, drying and roasting) on flavour precursors and pyrazines concentration of cocoa beans and its flavour quality evaluation. Fermentation was carried out in a rotary drum reactor by subjecting the mixed hybrid of cocoa beans to 6-day fermentation. During fermentation, effect of mass and turning time on the concentrations of these compounds were determined. Drying of cocoa beans was carried out in a hot air oven at an airflow of O.7m2/sec. Similarly, during drying, effect of bean depth and temperature were determined. Thirteen treatments of fermentation and drying were carried out according to a central composite rotatable design configuration for two factors. The effect of roasting on the concentrations of flavour precursors and pyrazines was compared with air-blown and sun-dried of drum and pod-storage fermentation and a tested representative Ghanaian sample. The resultant beans were made into cocoa liquor for flavour quality evaluation. Fermentation significantly decreased the concentration of acidic free amino acids in cocoa beans by 15%, whereas total, hydrophobic and other amino acids increased significantly by 148, 280 and 127%, respectively; peptide-N and total reducing sugars increased by 55 and 208%, respectively. The study found six types of pyrazines, with trimethyl- and tetramethylpyrazine being the major compounds. During cocoa fermentation, an increase in cocoa mass and turning time significantly increased the concentrations of flavour precursors and pyrazines. Results from the Response Surface Methodology (RSM) plots of hydrophobic free amino acids, peptide-N and total reducing sugars recommended mass and turning time for optimum condition of cocoa fermentation were at 60 kg and 5 min turning per day after 48 hr of fermentation. During drying, an increase in bean depth and temperature significantly decreased the concentrations of flavour precursors, but significantly increased the pyrazines concentration. In addition, total, acidic, hydrophobic and other amino acids decreased by 43, 41, 36 and 49%, respectively; peptide-N and total reducing sugars decreased by 56 and 71%, respectively; and trimethyl- and tetramethylpyrazine increased by 167 and 609%, respectively. Bean depth of 8.3 cm and temperature of 40°C were chosen as the optimum conditions for drying treatment. Under this condition, the concentrations of hydrophobic free amino acids,peptide-N and total reducing sugars were highly significant, whereas those of trimethyl-, tetramethyl- and total pyrazines were significantly low. Roasting the samples at 150°C for 30 min significantly decreased the concentrations of acidic, hydrophobic, total and other free amino acids, peptide-N and total reducing sugars but significantly increased the pyrazines concentration. There were no significant differences in the decrease of the concentration of hydrophobic free amino acids, peptide-N and total reducing sugars in the air-blown samples of different fermentation methods (drum and pod-storage); and in those of different drying treatments (air-blown and sun-dried). Air-blown drum fermentation samples had lower concentrations of 2,5-dimethyl-, trimethyl-, tetramethylpyrazine and total pyrazines than those of pod-stored (air-blown and sun-dried) and drum (sun-dried) samples.